Disposition of Policy Implementers: Study on The Hospitals Payment System Change in The Indonesian National Health Insurance Era - Abu Khoiri1,2, Widi Hidayat3 , Djazuly Chalidyanto4 , Fendy Suhariadi5 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Disposition of implementers to changes in hospitals payment system policies has becomean important issue in the implementation of the Indonesia National Health Insurance (NHI) program. Thechange from fee for services to a prospective payment system in the form of the Indonesia Case Based Group(INA-CBG) have caused low acceptance from clinicians. On the other side there was potential for fraud inthe hospitals claim collection scheme published by the corruption eradication commission. The objective ofthis study was to analyze the effect of disposition of implementers on financial pressure and fraud intention.Methods: The study used an observational analytic approach with a survey method, where researchersconducted observations, interviews and questionnaires. The research variables consist of disposition ofimplementers, financial pressure, and fraud intention. The research respondents were 110 physicians incharge of patients in 12 hospitals in East Java Indonesia. Data were analyzed by path analysis.Result: The direct causal effect of the disposition of implementers regarding the INA-CBG payment systemin hospitals to financial pressure had a value of p = 0.001 and B = -0.332.Conclussion: Disposition of implementers to changes in hospitals payment systems had a significant effecton financial pressure and fraud intention. A negative beta indicated that the disposition of implementers willhave an effect on increasing financial pressure.